The Russian Energy Policy on the International Scene - Y. V. Borovsky (Vestnik MGIMO-Universiteta)
The article is dedicated to a wide range of issues related to the Russian energy policy in the period 1992-2012, including an overview of the national energy strategy with a focus on international aspects; Russia’s participation in multilateral energy organizations and initiatives; the Russia-EU energy dialogue; Russia’s energy relations with CIS countries, and approaches of the Russian government to the diversification of energy export routes.